INTRAOCULAR PRESSURE LOWERING ACTIVITY OF OCUFORS® (FORSKOLIN 0.15% W/V OPHTHALMIC SOLUTION) IN WATER LOADED NEW ZEALAND WHITE RABBITS - MUHAMMED MAJEED,; KALYANAM NAGABHUSHANAM,; SANKARAN NATARAJAN,; PRITI VAIDYANATHAN,; SURESH KUMAR KARRI, (International Journal of Pharma and Bio Sciences, 2014)
Intra Ocular Pressure (IOP) is the fluid pressure inside the eye and is the most important risk factor for glaucoma. From the roots of Coleus forskohlii, an aromatic herb growing all over India, we extracted Forskolin. In this study we studied the IOP lowering activity of two strengths of Ocufors, viz., Ocufors® (Forskolin 1% w/v ophthalmic solution) and Ocufors® (Forskolin 0.15% w/v ophthalmic solution) in 12 New Zealand white rabbits, divided into three groups, four rabbits each. IOP was induced using water loading model in all three groups, as an acute model, with the right eye of all the animals received water for injection and thereby served as reference control. Whereas the left eye on all the three group animals received active drug, with Group 1 animals instilled with one drop of 1% w/v Forskolin solution while Group 2 and 3 animals instilled with one and two drops of 0.15% w/v Forskolin solution respectively. Post instillation of Forskolin 1% w/v ophthalmic solution (one drop), Forskolin 0.15% w/v ophthalmic solution, (one drop) and Forskolin 0.15% w/v ophthalmic solution (two drops) showed an IOP reduction of 23%, 19% and 30% at 45min, 45min and 75min respectively in New Zealand white rabbits, under test conditions employed. Forskolin aqueous clear ophthalmic solution showed a prolonged reducing effect on the IOP with one drop of 1% (w/v). However, a similar effect was noticed with two drops of 0.15% (w/v) Forskolin aqueous ophthalmic solution. Further clinical evaluation and confirmation of the low strength Ocufors (Forskolin 0.15% w/v) ophthalmic solution would help in replacing its higher strength counterpart (Forskolin 1% w/v) in mild open angle glaucoma patients.